Caracterización del sistema agroforestal de Caryodendron orinocense "metohuayo” y Cedrelinga cateniformis “tornillo" en Puerto Almendra, Loreto. 2022 - Chung Amasifuen, Leidy Yadira (2023)
The purpose of this research was to characterize the agroforestry system of Caryodendron orinocense "metohuayo" and Cedrelinga cateniformis "tornillo" in Puerto Almendra. The study was a quantitative, cross-sectional, descriptive, non-experimental research design. The population corresponded to all the plants located in the Center of Proceedings of Forest and Agricultural Species of the Faculty of Forestry Sciences of the National University of the Peruvian Amazon and the sample included all the plants of the metohuayo and tornillo agroforestry system. The results indicate that the natural fertility of the soils where the agroforestry system was established is low. However, the proposed system is applicable, taking with caution the results of the forestry component, which did not show a good reaction to external factors, leading to high mortality, so that the metohuayo has a survival rate of 68.50% and the tornillo 35.00% survival rate. For its part, the agricultural component shows that the banana exceeds 75.89% survival, cassava with a survival of 96.09%, pineapple with a survival of 64.58%, copoazú with a survival of 81.25% and, finally, the mandarin with a survival of 62.50%. In addition, yucca of two varieties included in the study were harvested.